2023
DOI: 10.1007/s10661-023-11867-6
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic studies of the removal of methylene blue from aqueous solution by biochar derived from jackfruit peel

Loc Ton-That,
Thi-Ngoc-Linh Huynh,
Bich-Ngoc Duong
et al.

Abstract: Kinetic studies play an instrumental role in determining the most appropriate reaction rate model for industrial-scale applications. This study focuses on the kinetics methylene blue (MB) adsorption from aqueous solutions by biochar derived from jackfruit peel. Various kinetic models, including pseudo-rstorder (PFO), pseudo-second-order (PSO), intra-diffusion, and Elovich models, were applied to study MB adsorption kinetics of jackfruit peel biochar. The experiments were performed with two initial concentratio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 81 publications
0
1
0
Order By: Relevance
“…It indicated that chemisorption was the main process for the adsorption of TC and LEV on TBI K . [43] Besides, it was found that the adsorption capacity of TBI K on LEV achieved 90 mg g -1 within 2 min whereas it was 17 min for TC (Figure S2a and b). Besides, a relatively quick equilibrium within 20 min was found and a larger q e,cal was achieved for MTL.…”
Section: Kineticsmentioning
confidence: 95%
“…It indicated that chemisorption was the main process for the adsorption of TC and LEV on TBI K . [43] Besides, it was found that the adsorption capacity of TBI K on LEV achieved 90 mg g -1 within 2 min whereas it was 17 min for TC (Figure S2a and b). Besides, a relatively quick equilibrium within 20 min was found and a larger q e,cal was achieved for MTL.…”
Section: Kineticsmentioning
confidence: 95%